Gonadal functional status and its correlation with body composition in adult men with non-diabetic chronic kidney disease non-dialysis-dependent stage - Raja Amarendra Muthina; Naveen Kumar Koppara; Vinapamula S. Kiranmayi; Suresh Vaikkakara; Sivakumar Vishnubotla (Journal of Clinical and Scientific Research)
Background: The study aims to evaluate the gonadal function in adult men non-diabetic chronic kidney disease (CKD) patients in the non-dialysis-dependent stage and its correlation with body composition. This was the first study done in India. Methods: This cross-sectional study was undertaken on 100 male CKD patients, aged ≥18 years, attending the nephrology outpatient department and was divided into two groups based on estimated glomerular filtration rate (eGFR). Serum creatinine, eGFR, haemoglobin, serum albumin, total testosterone, luteinising hormone (LH), follicle-stimulating hormone (FSH) and prolactin were estimated. Body composition was assessed using whole-body dual-energy X-ray absorptiometry. Results: Among the 100 patients, serum total testosterone levels ranged from 1.7 to 10.8 ng/mL with a mean value of 5.1 ± 1.5 ng/mL. Hypogonadism was found in 8% of patients. The median values of serum prolactin, serum FSH and serum LH were 10.3 (7.7–12.6) ng/mL, 11.3 (6.4–16.1) IU/L and 11.1 (7.1–15.6) IU/L, respectively. The means of bone mineral content and lean body mass were 2.5 ± 0.44 Kg and 42.3 ± 7.6 Kg, respectively. The median value of fat mass was 19.1 (14.8–22.4) Kg, and the mean fat percentage was 29.7 ± 5.1%. Serum testosterone levels had a significant positive correlation with eGFR levels, while a significant negative correlation with serum creatinine levels, serum prolactin levels, fat mass, percentage of fat, body mass index and lean body mass. Conclusions: Our study showed that with the worsening stage of CKD, there was a fall in serum testosterone levels and a rise in serum prolactin levels. Elevation of LH and FSH is a frequent finding in patients with CKD. Adiposity continues to have a negative impact on serum testosterone in CKD.